Zidebactam restores sulbactam susceptibility against carbapenem-resistant Acinetobacter baumannii isolates - Jose Cedano; Michelle Baez; Fernando Pasteran; Sabrina Daiana Montaña; Grace Ra; Venjaminne Fua; Alejandra Corso; Marcelo E. Tolmasky; Robert A. Bonomo; Robert A. Bonomo; Robert A. Bonomo; María Soledad Ramírez (Frontiers in Cellular and Infection Microbiology, 2022)
Carbapenems are commonly used to treat infections caused by multidrug-resistant (MDR) bacteria. Unfortunately, carbapenem resistance is increasingly reported in many gram-negative bacteria, especially Acinetobacter baumannii. Diazabicyclooctane (DBO) β-lactamase inhibitors, such as avibactam (AVI), when combined with sulbactam successfully restore sulbactam susceptibility against certain carbapenem-resistant A. baumannii (CRAB) isolates. In the present study, we tested zidebactam, a novel DBO with an additional mechanism of action, in combination with sulbactam against CRAB isolates, including strains that exhibited resistance against sulbactam/avibactam combination. A panel of 43 geographically and genetically distinct CRAB isolates recovered from different hospitals and containing different mechanisms of resistance were included in the present study. We also tested three reference strains (AB0057, AB5075, and AYE). Minimum inhibitory concentrations (MICs) for sulbactam (range 0.12–512 mg/l) and sulbactam plus 4 mg/l zidebactam were performed using microdilution according to CLSI Standards. A decrease ≥2 dilutions in sulbactam MICs was observed in 84% of the isolates when tested in combination with zidebactam. The sulbactam/zidebactam combination was able to restore sulbactam susceptibility in 91% of the isolates, including isolates that were resistant to sulbactam/avibactam combination. These data encouraged us to further explore sulbactam/zidebactam in other experimental models especially against CRAB isolates resistant to other DBOs.